Carbon-coated sodium ferrous sulfate phosphate positive electrode material as well as preparation method and application thereof

By using carbon coated sodium ferrous sulfate phosphate positive electrode material in sodium ion battery positive electrode material, and using solution system to prepare and coat conductive carbon material, the shortcomings of existing materials in terms of circulation performance, rate performance and air stability are solved. It realizes efficient and stable electrochemical performance and simple process.

CN119447266AActive Publication Date: 2025-02-14CENT SOUTH UNIV

Patent Information

Application Number
CN202411717921.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing sodium ion positive electrode materials have shortcomings in circulation performance, rate performance and air stability, and the preparation process is complex, making it difficult to achieve industrial production.

Method used

Carbon-coated sodium ferrous sulfate positive electrode material is prepared through a solution system, and the conductive carbon material is coated with sodium ferrous sulfate particles to improve the conductivity and air stability of the material.

Benefits of technology

It realizes a high voltage platform, excellent conductivity and good air stability, improves the circulation and rate performance of the material, and has a simple process and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447266A_ABST
    Figure CN119447266A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-coated sodium ferrous sulfate phosphate positive electrode material as well as a preparation method and application thereof. The carbon-coated sodium ferrous sulfate phosphate positive electrode material is square flaky particles formed by coating sodium ferrous sulfate phosphate with a conductive carbon material and irregular aggregates of the square flaky particles. The molecular formula of the sodium ferrous sulfate phosphate is Na (6-2x + y) Fex( SO4) (3-y) (PO4) y, x is more than 0 and less than 3, and y is more than 0 and less than or equal to 0.5. The invention also discloses a preparation method and application of the carbon-coated sodium ferrous sulfate phosphate positive electrode material. The positive electrode material has the advantages of phosphate and sulfate positive electrode materials, the voltage platform is high, the conductivity is excellent, the air stability is good, and the assembled battery has excellent chemical sodium storage performance, high discharge specific capacity, highly reversible charge-discharge reaction and good cycle performance. The method is simple in process, high in feasibility, low in raw material cost and easy to realize industrial production through a solution system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sodium ion positive electrode material and a preparation method and application thereof, and in particular to a carbon-coated sodium ferrous phosphate sulfate positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are secondary batteries that rely on the movement of sodium ions between positive and negative electrodes to complete charging and discharging. Their working principle is similar to that of widely used lithium-ion batteries. In recent years, as the global lithium resource supply faces bottlenecks, the price of lithium-ion batteries continues to rise, and with the continued growth of downstream battery demand and the continuous development of the energy storage market, sodium-ion batteries are favored because of their cleanliness and environmental protection, abundant raw material reserves, wide distribution, low price, higher safety and good high and low temperature performance. They have broad application prospects in power batteries, large-scale energy storage and other fields.

[0003] The main cathode materials for sodium-ion batteries are transition metal oxides, Prussian blue compounds, and polyanion compounds. There are more than 100 technical routes for sodium-ion cathode materials. Among them, layered oxides have high energy density but poor cycle performance; Prussian blue compounds have high energy density but have the risk of thermal runaway; common polyanion compounds have high cycle stability but poor conductivity; compared with PO 4 3- and P 2 O 7 4- , SO 4 2- With higher electronegativity and stronger inductive effect, the working voltage of sulfate-based polyanion cathode materials is higher. 4 2- The thermodynamic stability of sulfate positive electrode materials is poor, and they are easy to absorb water, which affects the ideal performance of the materials.

[0004] CN115020681A discloses a carbon-coated sodium iron sulfate positive electrode material and a preparation method thereof. Although the method has improved the problems of low sodium storage capacity, continuous decrease in working potential, poor cycle stability, poor rate performance and low-temperature working performance, etc., the method uses solid-phase ball milling for carbon coating, which is difficult to achieve uniform coating and large-scale production, and sulfate ions are easily deteriorated by water absorption when exposed to air, resulting in a certain degree of loss of electrochemical performance.

[0005] CN115050957A discloses a sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery. The positive electrode material introduces phosphate ions into the structure to improve its air stability and effectively avoid water absorption, decomposition and oxidation; at the same time, during the ball milling process, a conductive carbon material is added for coating to improve its conductivity. However, iron ions and phosphates will form iron phosphate precipitation in the liquid phase, and phosphate-containing iron-based composite polyanionic materials cannot be synthesized by liquid phase method, and the current preparation method based on solid phase ball milling is difficult to achieve mass production.

[0006] CN118299563A discloses a sodium ferrous sulfate phosphate polyanion positive electrode material and its preparation method and application, which is to mix the raw materials in proportion and vacuum concentrate, then dry and crystallize, and finally heat treat and form in an inert gas. However, its process is complicated, and the energy consumption generated during vacuum concentration and drying and crystallization is large, which is not conducive to energy-saving manufacturing.

[0007] CN118472239A discloses a doped sodium iron sulfate phosphate positive electrode material, a preparation method thereof, and a sodium ion battery. By doping a variety of multivalent metal elements and acid anions, the structure of the positive electrode material is improved, and the electrochemical performance and stability of the positive electrode material are also improved. However, its preparation process is long and the process steps are complicated. Under the sintering conditions, it is difficult to obtain a positive electrode material with good electrochemical performance.

[0008] Therefore, it is urgent to find a carbon-coated sodium ferrous phosphate sulfate positive electrode material and its application that has the advantages of both phosphate and sulfate positive electrode materials, a high voltage platform, excellent conductivity, good air stability, the assembled battery has excellent chemical sodium storage performance, high discharge specific capacity, highly reversible charge and discharge reaction, good cycle performance and rate performance, as well as a preparation method of the carbon-coated sodium ferrous phosphate sulfate positive electrode material with simple process, high feasibility, low raw material cost, and easy industrial production through a solution system. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a carbon-coated sodium ferrous phosphate sulfate positive electrode material and its application which has the advantages of both phosphate and sulfate positive electrode materials, a high voltage platform, excellent conductivity, and good air stability. The assembled battery has excellent chemical sodium storage performance, high discharge specific capacity, highly reversible charge and discharge reactions, and good cycle performance and rate performance.

[0010] The technical problem further to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing a carbon-coated sodium ferrous phosphate sulfate positive electrode material with simple process, high feasibility, low raw material cost and easy industrial production through a solution system.

[0011] The technical solution adopted by the present invention to solve the technical problem is as follows: a carbon-coated sodium ferrous phosphate sulfate positive electrode material, wherein the carbon-coated sodium ferrous phosphate sulfate positive electrode material is a square flaky particle and irregular agglomerates formed by a conductive carbon material coating sodium ferrous phosphate sulfate; the molecular formula of the sodium ferrous phosphate sulfate is Na (6-2x+y) Fe x (SO 4 ) (3-y) (PO 4 ) y , wherein 0<x<3 (more preferably 0.5≤x≤2.5), 0<y≤0.5 (more preferably 0.1≤y≤0.5). The chemical formula satisfies the charge balance. The sulfate has a high voltage platform, but it is easy to absorb moisture, resulting in structural changes, while the phosphate has a stable structure. After part of the phosphate is introduced into the sodium ferrous sulfate material in the form of anion substitution, it can not only ensure the high voltage platform of the material but also improve the air stability of the material. However, if the phosphate content continues to increase, it will lead to a decrease in electrochemical activity. The carbon-coated sodium ferrous phosphate sulfate positive electrode material has a smooth surface and is coated with a conductive carbon material, which is beneficial to improving electron transmission and increasing the ion deintercalation area.

[0012] Preferably, the mass fraction of the conductive carbon material in the carbon-coated sodium ferrous phosphate sulfate positive electrode material is 1.0-5.0% (more preferably 1.5-4.0%). The electronic conductivity of the polyanionic material is poor. By using an appropriate amount of conductive carbon material, the electronic conductivity can be improved. If too much conductive carbon material is added, the proportion of active substances will decrease, and the charge and discharge specific capacity of the material will decrease.

[0013] Preferably, the conductive carbon material includes one or more of conductive carbon black, carbon fiber, graphene, reduced graphene oxide, fullerene or carbon nanotube, etc. More preferably, the conductive carbon material is carbon nanotube, and the carbon nanotube has a tube length of 5 to 20 μm and a tube diameter of 10 to 20 nm.

[0014] Preferably, the average particle size of the square platelet particles is 1-5 μm, and the average thickness is 10-50 nm. Under the particle size, the material size uniformity is high, which is conducive to the stable performance of the material; under the thickness, the square platelet particles are easy to stack, which increases the contact area between particles, facilitates the rapid transmission of electrons, and improves the conductivity.

[0015] The technical solution adopted by the present invention to further solve the technical problem is as follows: a method for preparing a carbon-coated sodium ferrous phosphate sulfate positive electrode material, comprising the following steps: (1) dissolving a sodium source, a ferrous source and a sulfuric acid source in water, adjusting the pH value to acidic, and then sequentially adding a phosphoric acid source and a conductive carbon material slurry, stirring and mixing, to obtain a precursor solution; (2) After drying the precursor solution obtained in step (1), the obtained precursor powder is heat-treated under a protective atmosphere and cooled to room temperature in a furnace to obtain a carbon-coated sodium ferrous phosphate sulfate positive electrode material.

[0016] Preferably, in step (1), the molar volume ratio of the sodium ion, ferrous ion, sulfate ion, phosphate ion to water is 0.1-3.0 mol / L (more preferably 1-2 mol / L), 0.1-2.0 mol / L (more preferably 0.5-1.5 mol / L), 0.2-5.0 mol / L (more preferably 0.5-3.0 mol / L), 0.1-0.5 mol / L (more preferably 0.1-0.4 mol / L). In a mixed system, if the concentration is too low, the yield is insufficient; if the concentration is too high, it will cause segregation of excess components and it will be difficult to form a uniform mixture.

[0017] Preferably, in step (1), the mass fraction of the conductive carbon material slurry is 1-5%. If the mass fraction of the conductive carbon material slurry is too low, the volume of the conductive carbon material slurry added will be too large, which will dilute the concentration of the precursor solution; if the mass fraction of the conductive carbon material slurry is too high, the viscosity of the slurry will be too high, resulting in inaccurate solid content, so that the actual mass of the conductive carbon material slurry added is too high, thereby reducing the relative ratio of the active substance in the precursor solution.

[0018] Preferably, in step (1), the amount of the conductive carbon material slurry is such that the conductive carbon material accounts for 1-5% (more preferably 1.5-4.0%) of the theoretical mass of the final product of the carbon-coated sodium ferrous phosphate sulfate positive electrode material. If the amount of the conductive carbon material slurry is too low, the conductivity of the material is poor and the electrochemical activity of the active material cannot be fully exerted; if the amount of the conductive carbon material slurry is too high, the relative ratio of the active material in the precursor solution will be reduced.

[0019] Preferably, in step (1), the pH value is adjusted to 3 to 4. In the pH range, ferrous ions will not be oxidized to ferric ions; at the same time, since ferrous phosphate is easily soluble in an acidic environment, even if phosphate is added later, ferrous phosphate precipitation will not be formed, and industrial production can be achieved.

[0020] Preferably, in step (1), an acidic or alkaline medium solution with a mass fraction of 5 to 20% is added dropwise to adjust the pH value. If the mass fraction is too low, the pH value adjustment process is too long, and if the mass fraction is too high, the acidity and alkalinity control range is difficult to control.

[0021] Preferably, in step (1), the acidic medium solution includes one or more of dilute sulfuric acid, ascorbic acid solution or citric acid solution. When the acidic medium solution is dilute sulfuric acid, adding a sulfuric acid source and adjusting the pH value can be performed simultaneously, in order to simultaneously meet the sulfate content and pH value. The acidic medium can slow down the oxidation rate of the ferrous source, thereby extending its service life; in addition, since phosphate is a weak acid salt, according to the principle of strong acid to weak acid, no ferrous phosphate precipitate will be generated under the acidic conditions.

[0022] Preferably, in step (1), the alkaline medium solution comprises one or more of sodium hydroxide solution, sodium carbonate solution or ammonia solution. When the alkaline medium solution is sodium hydroxide solution or sodium carbonate solution, adding a sodium source and adjusting the pH value can be performed simultaneously, so as to simultaneously meet the sodium ion content and pH value.

[0023] Preferably, in step (1), the stirring and mixing temperature is 20 to 50° C., the stirring speed is 300 to 600 r / min (more preferably 350 to 500 r / min), and the time is 5 to 60 min (more preferably 10 to 40 min). During the stirring process, the precursor ions, acid radicals and conductive carbon materials are fully mixed, which helps to form a uniform and stable precursor powder during the spray drying process.

[0024] Preferably, in step (1), the sodium source includes one or more of sodium sulfate, sodium carbonate, sodium hydroxide, sodium nitrate or sodium phosphate, and hydrates thereof. When the sodium source is sodium phosphate, it is added as a phosphoric acid source after adjusting the pH value.

[0025] Preferably, in step (1), the ferrous source includes one or more of ferrous sulfate and its hydrate.

[0026] Preferably, in step (1), the sulfuric acid source includes one or more of sodium sulfate, ferrous sulfate, and hydrates thereof or sulfuric acid, etc. When the sulfuric acid source contains sodium or ferrous sulfate at the same time, the sulfuric acid source can be used as a sodium source or a ferrous source at the same time.

[0027] Preferably, in step (1), the phosphate source includes one or more of diammonium phosphate, diammonium hydrogen phosphate, sodium phosphate, and hydrates thereof or phosphoric acid, etc. When the phosphate source also contains sodium, the phosphate source can also serve as a sodium source.

[0028] Preferably, in step (1), the conductive carbon material includes one or more of conductive carbon black, carbon fiber, graphene, reduced graphene oxide, fullerene or carbon nanotube.

[0029] Preferably, in step (2), the drying is spray drying or freeze drying, etc. The solvent can be removed during the drying process, and a square platelet-shaped particle morphology is formed.

[0030] Preferably, in step (2), the temperature of the spray drying is 150-240°C, and the creeping speed is 20-65rpm. During the spray drying molding process, the solvent in the precursor solution can be quickly removed in a short time, and during the dehydration process of the acidic solvent, sulfate and phosphate will combine with ferrous and sodium ions, and at the same time, the surface tension will reach equilibrium. At this time, the solute first forms nano-scale particles, that is, forms a lamellar particle morphology, and gradually aggregates during the heating process to form micron-scale aggregates. During the spray drying process, the higher the temperature, the more complete the solvent removal, and the drier the resulting precursor powder, but the spray dryer is more damaged; the creeping speed affects the output of the dried precursor powder per unit time. Within the parameter range, the precursor powder has a good drying effect and a high yield.

[0031] Preferably, in step (2), the protective atmosphere comprises one or more of nitrogen, argon or helium, etc. The protective atmosphere used in the present invention is a high-purity atmosphere with a purity of ≥99.9%.

[0032] Preferably, in step (2), before the heat treatment, a protective atmosphere is introduced for 0.5 to 3.0 hours and the heat treatment device is emptied.

[0033] Preferably, in step (2), the heat treatment is carried out at a rate of 1 to 10°C / min, from room temperature to 350 to 400°C, and then kept at this temperature for 6 to 24 hours (more preferably 10 to 20 hours). 4 2- At 350℃, the crystal of the material is difficult to form, while SO 4 2- Above 400°C, it is easy to decompose. Heat treatment within the temperature and time range will reduce the generation of iron oxide and sodium sulfate, so that the dried precursor powder is gradually formed into sodium ferrous phosphate sulfate crystals.

[0034] The technical solution adopted by the present invention to further solve its technical problem is as follows: an application of a carbon-coated sodium ferrous phosphate sulfate positive electrode material, and the positive electrode sheet made of the carbon-coated sodium ferrous phosphate sulfate positive electrode material is used to assemble button-type, cylindrical, square or soft-pack sodium ion batteries.

[0035] The beneficial effects of the present invention are as follows: (1) The carbon-coated sodium ferrous phosphate sulfate positive electrode material of the present invention combines the advantages of the high working voltage platform of sulfate and the high air stability of phosphate, overcomes the defect of the low voltage platform of phosphate positive electrode material, and the voltage platform of the carbon-coated sodium ferrous phosphate sulfate positive electrode material is increased to 3.7V; overcomes the technical difficulties of easy water absorption, easy deterioration and low gram capacity of sulfate positive electrode material, reduces the water absorption and oxidizability of sulfate positive electrode material, and effectively improves the air stability; therefore, the carbon-coated sodium ferrous phosphate sulfate positive electrode material of the present invention has the advantages of both phosphate and sulfate positive electrode materials; in addition, by coating with conductive carbon material, the conductivity of the carbon-coated sodium ferrous phosphate sulfate positive electrode material of the present invention is greatly improved; (2) The battery assembled with the sodium ion battery positive electrode made of the carbon-coated sodium ferrous phosphate sulfate positive electrode material of the present invention has excellent chemical sodium storage performance, high discharge specific capacity, highly reversible charge and discharge reaction, and excellent cycle performance and rate performance; the assembled battery has a discharge specific capacity of 93.18 mAh / g and 88.80 mAh / g, respectively, and a charge specific capacity of 101.99 mAh / g and 89.62 mAh / g, respectively, and a coulombic efficiency of 91.36% and 99.09%, respectively, after 100 cycles at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 0.1 C (11 mA / g, first 3 cycles) for the first time and at a rate of 1 C (110 mA / g, starting from the 4th cycle), respectively, indicating that the material The charge and discharge reaction of the material is highly reversible; at a charge and discharge voltage of 2 to 4.5V and a rate of 1C (110mA / g), starting from the 4th cycle, the discharge specific capacity can be as high as 91.52mAh / g. After 100 cycles, the discharge specific capacity can be as high as 88.80mAh / g, and the capacity retention rate can be as high as 97.03%. The cycle performance is excellent, indicating that the material structure is stable, the crystal deformation is small, and the sodium ion deintercalation channel is low; after 13 rates from 0.1C to 10C and 65 cycles of testing, the discharge specific capacity can still be as high as 87.82mAh / g, and the capacity retention rate can be as high as 97.60%. The rate performance is excellent, indicating that during the high-rate charge and discharge process, the material crystal structure is stable and the sodium ion deintercalation rate is fast; After being exposed to air for a week, the assembled battery was cycled for 100 cycles at a charge and discharge voltage of 2.0-4.5V, 0.1C (11mA / g, first 3 cycles) rate for the first time, and 1C rate (110mA / g, starting from the 4th cycle). The discharge specific capacity was 92.71mAh / g and 86.73mAh / g, respectively. The charge specific capacity was 105.08mAh / g and 87.89mAh / g, respectively. The coulombic efficiency was 88.23% and 98.68%, respectively. This shows that the charge and discharge reaction of the material is still highly reversible; at a charge and discharge voltage of 2 to 4.5 V and a rate of 1C (110 mA / g), starting from the 4th cycle, the discharge specific capacity can reach 91.52 mAh / g. After 100 cycles, the discharge specific capacity can reach 86.73 mAh / g, and the capacity retention rate can reach 94.77%. The cycle performance is still excellent, indicating that the introduction of phosphate anions can slow down the hygroscopicity of sodium iron sulfate to a certain extent, allowing the material to maintain stable electrochemical activity. (3) The method of the present invention has simple process, high feasibility, low raw material cost, and can be easily industrialized through a solution system. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The carbon nanotubes coated with Na in Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 SEM images of the cathode material (a), (b) and its SEM image after exposure to air for one week (c); Figure 2 The carbon nanotubes coated with Na in Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The cathode material and its XRD pattern after being exposed to air for one week; Figure 3 The carbon nanotubes coated with Na in Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 Raman spectra of cathode materials (where the three curves represent parallel samples collected in three different areas); Figure 4 The carbon nanotubes coated with Na in Example 1 of the present invention 2.9 Fe 1.7 (SO 4 )2.7 (PO 4 ) 0.3 The charge and discharge curves of the first and 100th cycles of the battery assembled with the positive electrode material and the electrode made after being exposed to air for one week; Figure 5 The carbon nanotubes coated with Na in Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The discharge capacity of the battery assembled from the positive electrode material and the electrode made after exposure to air for one week after 100 cycles; Figure 6 The carbon nanotubes coated with Na in Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 Rate performance diagram of cathode materials; Figure 7 The carbon nanotubes coated with Na in Example 2 of the present invention 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 SEM image of the cathode material; Figure 8 The carbon nanotubes coated with Na in Example 2 of the present invention 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 XRD pattern of positive electrode material; Fig. 9 The carbon nanotubes coated with Na in Example 2 of the present invention 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The charge and discharge curves of the battery assembled with electrodes made of positive electrode materials for the first and 100th cycles; Fig.10 The carbon nanotubes coated with Na in Example 2 of the present invention 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The discharge capacity diagram of the battery assembled with electrodes made of positive electrode materials after 100 cycles; Fig.11 The carbon nanotubes coated with Na obtained in Comparative Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 SEM image of the cathode material; Fig.12 The carbon nanotubes coated with Na obtained in Comparative Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 XRD pattern of positive electrode material; Fig.13 The carbon nanotubes coated with Na obtained in Comparative Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The charge and discharge curves of the battery assembled with electrodes made of positive electrode materials for the first and 100th cycles; Fig.14 The carbon nanotubes coated with Na obtained in Comparative Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The discharge capacity diagram of the battery assembled with electrodes made of positive electrode materials after 100 cycles; Fig.15 The carbon nanotubes coated with Na obtained in Comparative Example 2 of the present invention 2.6 Fe 1.7 (SO 4 ) 3 SEM image of the cathode material (a) and its SEM image after exposure to air for one week (b); Fig.16 The carbon nanotubes coated with Na obtained in Comparative Example 2 of the present invention 2.6 Fe 1.7 (SO 4 ) 3 The cathode material and its XRD pattern after being exposed to air for one week; Fig.17 The carbon nanotubes coated with Na obtained in Comparative Example 2 of the present invention 2.6 Fe 1.7 (SO 4 ) 3The charge and discharge curves of the first and 100th cycles of the battery assembled with the positive electrode material and the electrode made after being exposed to air for one week; Fig.18 The carbon nanotubes coated with Na obtained in Comparative Example 2 of the present invention 2.6 Fe 1.7 (SO 4 ) 3 The discharge capacity diagram of the battery assembled from the positive electrode material and the electrode made after being exposed to air for one week and cycled 100 times; Fig.19 The carbon nanotubes coated with Na obtained in comparative example 3 of the present invention at different heat treatment temperatures 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 XRD pattern of the positive electrode material. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the embodiments and drawings.

[0038] The carbon nanotube slurry used in the embodiments of the present invention and the comparative examples was purchased from Xiamen Kaina Graphene Technology Co., Ltd. The carbon nanotubes have a tube length of 5 to 20 μm and a tube diameter of 10 to 20 nm. The protective atmosphere used is a high-purity atmosphere with a purity of ≥99.9%. The raw materials or chemical reagents used in the embodiments of the present invention and the comparative examples, unless otherwise specified, are obtained through conventional commercial channels.

[0039] A carbon nanotube coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 Positive electrode material example 1 The carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The positive electrode material is carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The square flake particles and irregular agglomerates formed; the carbon nanotubes are coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO4 ) 0.3 The mass fraction in the positive electrode material is 2.3%; the average particle size of the square flake particles is 4 μm, and the average thickness is 30 nm.

[0040] In order to verify the air stability of the positive electrode material, the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The positive electrode material was exposed to air for one week, wherein the average temperature of the air was 30°C and the average humidity was 50%.

[0041] like Figure 1 (a) shows that the carbon nanotubes coated with Na in Example 1 of the present invention 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The morphology of the positive electrode material is square flake particles and irregular agglomerates thereof, wherein the average particle size of the square flake particles is 4 μm, the average thickness is 30 nm, and the Figure 1 (b) Carbon nanotubes were observed to be randomly distributed on the surface of square platelet particles; Figure 1 (c) shows that the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 After the cathode material was exposed to air for one week, its morphology did not change significantly.

[0042] The results of the sulfur-carbon analyzer show that the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The mass fraction of carbon nanotubes in the positive electrode material is 2.3%.

[0043] like Figure 2 As shown, in Example 1 of the present invention, carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 In the positive electrode material, in addition to Na 2.5 Fe 1.75 (SO4 ) 3 -In addition to the typical characteristic peaks of PDF#97-025-2404, NaFePO was also found at 2x diffraction angles of 20.146°, 23.980°, 32.799°, 33.118°, 34.716°, 48.327°, and 49.049°. 4 -PDF#97-008-5671, but the peaks are not completely present, confirming that the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The positive electrode material is not a simple mixture of sodium iron sulfate and sodium iron phosphate; Example 1 of the present invention carbon nanotube coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 After the positive electrode material was exposed to air for one week, its crystal structure had almost no significant change, indicating that the carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The positive electrode material hardly reacts with water molecules and has good air stability.

[0044] like Figure 3 As shown, in Example 1 of the present invention, carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 In the positive electrode material, it was found that -1 PO 4 3- Raman reflection due to group vibration is located at 590.5cm -1 The peak at SO 4 2- Vibration is related, indicating that the present invention embodiment 1 carbon nanotubes coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 SO is present in the cathode material4 2- and PO 4 3- group; among them, 1350cm -1 The D band peak near 1590cm represents the introduction of sp3 hybridized carbon atoms or the defects of sp2 hybridized network structure, and its intensity corresponds to the degree of defects in carbon nanotubes; -1 The nearby G band peak represents the regular graphene structure of the E2g vibration mode due to sp2 hybridized carbon atoms, and its intensity corresponds to the integrity of the carbon nanotube.

[0045] A carbon nanotube coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 Preparation method of positive electrode material Example 1 (1) 14.2042 g (0.1 mol) of anhydrous sodium sulfate and 47.2617 g (0.17 mol) of ferrous sulfate heptahydrate were dissolved in 200 mL of deionized water, and a 5% by mass fraction dilute sulfuric acid solution was added dropwise to adjust the pH value to 4. Then, 11.4042 g (0.03 mol) of sodium phosphate dodecahydrate and 21.2 g of a 5% by mass fraction carbon nanotube slurry were added in sequence, and the mixture was stirred and mixed at 25° C. and a stirring speed of 350 r / min for 30 min to obtain a precursor solution; (2) The precursor solution obtained in step (1) was spray dried at 220°C and a creep speed of 35 rpm, and the obtained precursor powder was placed in a corundum magnetic boat and placed in a tube furnace. A high-purity argon atmosphere was first introduced for 2 hours, and the tube furnace was evacuated. Then, the temperature was raised from room temperature to 400°C at a rate of 2°C / min in the high-purity argon atmosphere, and the temperature was kept at that temperature for 12 hours for heat treatment. The carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 Positive electrode material.

[0046] A carbon nanotube coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 Application Example 1 of Positive Electrode Material The carbon nanotubes of Example 1 of the present invention are coated with Na 2.9 Fe 1.7 (SO 4 )2.7 (PO 4 ) 0.3 The positive electrode sheet made of positive electrode material is used to assemble button-type sodium ion batteries.

[0047] The preparation method of the positive electrode sheet is as follows: weigh 0.8 g of the carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The positive electrode material is prepared by adding 0.1 g of conductive carbon black SP as a conductive agent and 0.1 g of PVDF polyvinylidene fluoride as a binder, and using N-methylpyrrolidone as a solvent, mixing and grinding to form a positive electrode material.

[0048] The battery assembly method is as follows: the positive electrode material is coated on the surface of aluminum foil to form an electrode sheet, and then, in a closed glove box filled with an inert atmosphere, the electrode sheet is used as the positive electrode, the metal sodium sheet is used as the negative electrode, the glass fiber membrane is used as the separator, and 1 mol / L NaClO 4 / EC:DMC (volume ratio 1:1) containing 5.0% FEC as the electrolyte was assembled into CR2032 button cells for charge and discharge tests.

[0049] like Figure 4 As shown, in Example 1 of the present invention, carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The battery assembled with electrodes made of positive electrode materials has a discharge capacity of 93.18 mAh / g and 88.80 mAh / g, respectively, and a charge capacity of 101.99 mAh / g and 89.62 mAh / g, respectively, and a coulombic efficiency of 91.36% and 99.09%, respectively, at a charge and discharge voltage of 2 to 4.5 V, a rate of 0.1 C (11 mA / g, first 3 cycles), and a rate of 1 C (110 mA / g, starting from the 4th cycle) after 100 cycles, indicating that the material has a good first effect and a high discharge capacity. Example 1 of the present invention: Carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3After the positive electrode material was exposed to air for one week, the battery assembled with the prepared electrode had a discharge capacity of 92.71 mAh / g and 86.73 mAh / g at a charge and discharge voltage of 2 to 4.5 V and a rate of 0.1 C (11 mA / g, first 3 cycles) for the first time and 1 C rate (110 mA / g, starting from the 4th cycle) for 100 cycles. The charge capacity was 105.08 mAh / g and 87.89 mAh / g, and the coulombic efficiency was 88.23% and 98.68%, respectively; This shows that the present invention embodiment 1 carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 After the positive electrode material was exposed to air for one week, the initial charge and discharge specific capacity had almost no significant change, indicating that the carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The positive electrode material can maintain its structure in the air and has good air stability. It can maintain structural stability during the charge and discharge process, has small volume expansion, and good conductivity, making the charge and discharge reactions highly reversible.

[0050] like Figure 5 As shown, in Example 1 of the present invention, carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The battery assembled with the electrode made of the positive electrode material has a discharge capacity of 91.52 mAh / g from the 4th cycle at a charge and discharge voltage of 2 to 4.5 V and a rate of 1C (110 mA / g). After 100 cycles, the discharge capacity is 88.80 mAh / g, and the capacity retention rate is 97.03%; Example 1 of the present invention: Carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 After the positive electrode material was exposed to the air for one week, the battery assembled with the prepared electrodes had a discharge capacity of 91.52 mAh / g starting from the 4th cycle at a charge and discharge voltage of 2 to 4.5 V and a rate of 1C (110 mA / g). After 100 cycles, the discharge capacity was 86.73 mAh / g, and the capacity retention rate was 94.77%, indicating that the material has good structural stability, a high cycle life, and good air stability.

[0051] like Figure 6 As shown, in Example 1 of the present invention, carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The battery assembled with electrodes made of positive electrode materials has a charge and discharge voltage of 2 to 4.5V, and after 65 cycles of testing at 13 rates from 0.1C to 10C, the discharge specific capacity can still reach 87.82 mAh / g, and the capacity retention rate is 97.60%. The rate performance is excellent, indicating that during the high-rate charge and discharge process, the material's crystal structure is stable and the sodium ion deintercalation rate is fast.

[0052] A carbon nanotube coated Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 Positive electrode material embodiment 2 The carbon nanotube-coated Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The positive electrode material is carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.3 The square flake particles and irregular agglomerates formed; the carbon nanotubes are coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The mass fraction in the positive electrode material is 3.3%; the average particle size of the square flake particles is 3 μm, and the average thickness is 30 nm.

[0053] like Figure 7 As shown, in Example 2 of the present invention, carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The morphology of the positive electrode material is square flake particles and irregular agglomerates thereof. The average particle size of the square flake particles is 3 μm, the average thickness is 30 nm, and it can be observed that carbon nanotubes are randomly distributed on the surface of the square flake particles.

[0054] The results of the sulfur-carbon analyzer show that the carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The mass fraction of carbon nanotubes in the positive electrode material is 3.3%.

[0055] like Figure 8 As shown, in Example 2 of the present invention, carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 In the positive electrode material, the carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The crystal structure of the positive electrode material is consistent, and NaFePO is also found at 2x diffraction angles of 20.146°, 23.980°, 32.799°, 33.118°, 34.716°, 48.327°, and 49.049°. 4 -PDF#97-008-5671, but the peaks are not completely present, confirming that the carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The positive electrode material is not a simple mixture of sodium iron sulfate and sodium iron phosphate.

[0056] After testing, the carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 In the positive electrode material, it was found that -1 PO 4 3- Raman reflection due to group vibration is located at 590.5cm -1 The peak at SO 4 2- Vibration is related, indicating that the carbon nanotubes coated with Na in Example 2 of the present invention3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 SO is present in the cathode material 4 2- and PO 4 3- group; among them, 1350cm -1 The D band peak near 1590cm represents the introduction of sp3 hybridized carbon atoms or the defects of sp2 hybridized network structure, and its intensity corresponds to the degree of defects in carbon nanotubes; -1 The nearby G band peak represents the regular graphene structure of the E2g vibration mode due to sp2 hybridized carbon atoms, and its intensity corresponds to the integrity of the carbon nanotube.

[0057] A carbon nanotube coated Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 Example 2 of Preparation Method of Positive Electrode Material (1) 11.3633 g (0.08 mol) of anhydrous sodium sulfate and 47.2617 g (0.17 mol) of ferrous sulfate heptahydrate were dissolved in 200 mL of deionized water, and a 5% by mass ascorbic acid solution was added dropwise to adjust the pH value to 3.5. Then, 19.01 g (0.05 mol) of sodium phosphate dodecahydrate and 31.0 g of a 5% by mass carbon nanotube slurry were added in sequence, and the mixture was stirred at 30° C. and a stirring speed of 400 r / min for 35 min to obtain a precursor solution. (2) The precursor solution obtained in step (1) was spray dried at 200°C and a creep speed of 45 rpm, and the obtained precursor powder was placed in a corundum magnetic boat and placed in a tubular furnace. A high-purity argon atmosphere was first introduced for 2 hours, and the tubular furnace was evacuated. Then, the temperature was raised from room temperature to 350°C at a rate of 5°C / min in a high-purity argon atmosphere, and the temperature was kept at that temperature for 16 hours for heat treatment. The carbon nanotube-coated Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 Positive electrode material.

[0058] A carbon nanotube coated Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 )0.5 Application Example 2 of Positive Electrode Material The carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The positive electrode sheet made of positive electrode material is used to assemble button-type sodium ion batteries.

[0059] The preparation method of the positive electrode plate and the battery assembly method are the same as those in method embodiment 1.

[0060] like Fig. 9 As shown, in Example 2 of the present invention, carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The battery assembled with electrodes made of positive electrode materials has a discharge capacity of 91.77mAh / g and 85.86mAh / g, respectively, and a charge capacity of 102.65mAh / g and 86.82mAh / g, respectively, after 100 cycles at a charge and discharge voltage of 2 to 4.5V and a rate of 0.1C (11mA / g, first 3 cycles) for the first time and 1C rate (110mA / g, starting from the 4th cycle). The coulomb efficiency is 89.40% and 98.89%, respectively, indicating that the material has a good first effect and a high discharge capacity.

[0061] Fig.10 As shown, in Example 2 of the present invention, carbon nanotubes coated with Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5 The battery assembled with electrodes made of positive electrode materials has a discharge capacity of 89.72 mAh / g starting from the 4th cycle at a charge and discharge voltage of 2 to 4.5 V and a rate of 1C (110 mA / g). After 100 cycles, the discharge capacity is 85.86 mAh / g, and the capacity retention rate is 95.70%, indicating that the material has good structural stability and a high cycle life.

[0062] It has been verified that the present invention uses the carbon nanotube-coated Na 3.1 Fe 1.7 (SO 4 ) 2.5 (PO 4 ) 0.5The battery assembled with electrodes made of positive electrode materials has a discharge capacity of 85.36 mAh / g and a capacity retention rate of 95.14% at a charge and discharge voltage of 2 to 4.5 V. The rate performance is excellent, indicating that during the high-rate charge and discharge process, the crystal structure of the material is stable and the sodium ion deintercalation rate is fast.

[0063] Comparative Example 1 (1) 14.2042 g (0.1 mol) of anhydrous sodium sulfate and 47.2617 g (0.17 mol) of ferrous sulfate heptahydrate were mixed evenly, and then 11.4042 g (0.03 mol) of sodium phosphate dodecahydrate and 21.2 g of carbon nanotube slurry with a mass fraction of 5% were added in sequence, and the mixture was placed in a ball mill and ball milled at 500 r / min for 10 h to obtain a precursor powder; (2) The precursor powder obtained in step (1) is placed in a corundum magnetic boat, placed in a tube furnace, and first introduced into a high-purity argon atmosphere for 2 hours, the tube furnace is evacuated, and then heated from room temperature to 400°C at a rate of 2°C / min in a high-purity argon atmosphere, and then kept at this temperature for 12 hours for heat treatment, and then cooled to room temperature with the furnace to obtain carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 Positive electrode material.

[0064] like Fig.11 As shown, the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The positive electrode material is carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The formed micron-sized irregular particles have poor uniformity.

[0065] like Fig.12 As shown, the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 In the positive electrode material, its crystal structure is similar to that of the carbon nanotube-coated Na 2.9 Fe 1.7 (SO4 ) 2.7 (PO 4 ) 0.3 There are some differences in the positive electrode materials, and the characteristic peak intensity changes. Only NaFePO 4 -PDF#97-008-5671 (220), (121), (301) and (222) weak characteristic peaks, indicating that the carbon nanotubes obtained by ball milling in Comparative Example 1 of the present invention are coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The crystal forming degree of the positive electrode material is poor.

[0066] The carbon nanotubes obtained in Comparative Example 1 of the present invention are coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The positive electrode sheet made of positive electrode material is used to assemble button-type sodium ion batteries.

[0067] The preparation method of the positive electrode plate and the battery assembly method are the same as those in method embodiment 1.

[0068] like Fig.13 As shown, the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The battery assembled with the electrode made of the positive electrode material has a first discharge capacity of 87.65 mAh / g and a first charge capacity of 100.36 mAh / g at a charge and discharge voltage of 2 to 4.5 V and a rate of 0.1 C (11 mA / g), and a coulombic efficiency of 87.34%, which is higher than that of the carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The first discharge specific capacity of the positive electrode material decreased by about 5.5 mAh / g, indicating that the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3The nano-scale square flake particles and their irregular agglomerate morphology of the positive electrode material have a certain effect of improving the specific capacity.

[0069] like Fig.14 As shown, the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The battery assembled with electrodes made of positive electrode materials has a discharge capacity of 86.04 mAh / g starting from the 4th cycle at a charge and discharge voltage of 2 to 4.5 V and a rate of 1C (110 mA / g). After 100 cycles, the discharge capacity is 83.36 mAh / g, and the capacity retention rate is 96.89%.

[0070] It has been verified that the carbon nanotubes coated with Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The battery assembled with the electrode made of the positive electrode material has a charge and discharge voltage of 2 to 4.5 V, and after 65 cycles of 13 rates from 0.1C to 10C, the discharge specific capacity is only 79.26 mAh / g, and the capacity retention rate is only 90.43%. The rate performance is significantly lower than that of the application example 1 of the present invention, indicating that the carbon nanotubes coated with Na obtained by ball milling method are 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 During high-rate charge and discharge of the positive electrode material, the crystal structure stability of the material is poor and the sodium ion deintercalation is hindered.

[0071] Comparative Example 2 (1) Dissolve 18.4655 g (0.13 mol) of anhydrous sodium sulfate and 47.2617 g (0.17 mol) of ferrous sulfate heptahydrate in 200 mL of deionized water, mix well, then add 26.2908 g of carbon nanotube slurry with a mass fraction of 5%, stir and mix at 25°C and a stirring speed of 350 r / min for 30 min to obtain a precursor solution; (2) The same method as step (2) of Example 1 is used to obtain carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 Positive electrode material.

[0072] In order to verify the effect of non-acidic reaction system and no introduction of phosphate on the air stability of the material, the carbon nanotubes obtained in Comparative Example 2 of the present invention were coated with Na 2.6 Fe 1.7 (SO 4 ) 3 The positive electrode material was exposed to air for one week, wherein the average temperature of the air was 30°C and the average humidity was 50%.

[0073] like Fig.15 As shown in (a), the carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 The positive electrode material is carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 The micrometer-sized regular spherical particles formed are of uneven size, and carbon nanotubes can be observed mixed with them; Fig.15 As shown in (b), the carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 After being exposed to the air for a week, the positive electrode material could hardly maintain its typical spherical particle structure, with obvious water absorption and dissolution on the surface and uneven size.

[0074] like Fig.16 As shown, the carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 In the positive electrode material, its crystal structure is similar to Na 2.5 Fe 1.75 (SO 4 ) 3 -PDF#97-025-2404 completely corresponds to the typical characteristic peaks, indicating that the carbon nanotubes obtained in Comparative Example 2 of the present invention are coated with Na 2.6 Fe 1.7 (SO 4 ) 3 The positive electrode material has high phase purity; however, after being exposed to air for one week, many obvious characteristic peaks can be observed at a 2x diffraction angle of about 20°, which is attributed to the carbon nanotubes coated with Na obtained in Comparative Example 2 of the present invention. 2.6 Fe 1.7 (SO 4 ) 3 The positive electrode material absorbs moisture from the air to form Na 2 Fe(SO 4 ) 2·4H 2 O phase, indicating that the carbon nanotubes obtained in Comparative Example 2 of the present invention are coated with Na 2.6 Fe 1.7 (SO 4 ) 3 After the positive electrode material was exposed to the air for one week, the physical purity was not high, impurities existed, and the air stability was poor.

[0075] like Fig.17 As shown, the carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 The battery assembled with the electrode made of the positive electrode material, after the charge and discharge voltage is 2-4.5V, the first cycle at 0.1C (11mA / g, the first 3 cycles) rate and the cycle at 1C rate (110mA / g, starting from the 4th cycle) for 100 cycles, the discharge specific capacity is 85.26mAh / g, 80.61mAh / g, the charge specific capacity is 99.94mAh / g, 82.04mAh / g, and the coulomb efficiency is 85.31% and 98.26%, respectively, compared with the carbon nanotube-coated Na in Example 1 of the present invention. 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The first discharge capacity of the positive electrode material decreased by about 8 mAh / g, indicating that PO 4 2- The addition of can improve the initial charge and discharge specific capacity and coulombic efficiency of the positive electrode material; the carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 After the positive electrode material was exposed to air for one week, the battery assembled with the prepared electrode had a discharge capacity of 75.90 mAh / g and 58.67 mAh / g, respectively, a charge capacity of 91.21 mAh / g and 60.09 mAh / g, respectively, and a coulombic efficiency of 83.21% and 97.64%, respectively, at a charge and discharge voltage of 2 to 4.5 V, a rate of 0.1 C (11 mA / g, first 3 cycles), and a rate of 1 C (110 mA / g, starting from the 4th cycle) for the first time after 100 cycles. Compared with the carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 The first discharge capacity of the positive electrode material decreased by about 16.8 mAh / g, indicating that PO 4 2-The addition of can improve the air stability of the material, enhance its resistance to water absorption, and stabilize its crystal structure and electrochemical activity.

[0076] like Fig.18 As shown, the carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 The battery assembled with the electrode made of the positive electrode material has a discharge capacity of 82.82 mAh / g from the 4th cycle at a charge and discharge voltage of 2 to 4.5 V and a rate of 1C (110 mA / g). After 100 cycles, the discharge capacity is 80.39 mAh / g, and the capacity retention rate is 97.07%; the carbon nanotube-coated Na 2.6 Fe 1.7 (SO 4 ) 3 After the positive electrode material was exposed to air for one week, the battery assembled with the prepared electrode had a discharge capacity of 66.14 mAh / g from the 4th cycle at a charge and discharge voltage of 2 to 4.5 V and a rate of 1C (110 mA / g). After 100 cycles, the discharge capacity was 58.67 mAh / g, and the capacity retention rate was only 88.71%, indicating that the carbon nanotube-coated Na 2.6 Fe 1.7 (SO 4 ) 3 The air stability is poor, the water absorption capacity is strong, the material crystal is easy to deform, and the electrochemical activity decreases quickly.

[0077] It has been verified that the carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 The battery assembled with the electrode made of the positive electrode material has a charge and discharge voltage of 2 to 4.5 V, and after 65 cycles of 13 rates from 0.1C to 10C, the discharge specific capacity is only 68.74 mAh / g, and the capacity retention rate is 90.57%. The rate performance is significantly lower than that of the application example 1 of the present invention, indicating that there is no PO 4 2- The introduced carbon nanotubes coated with Na 2.6 Fe 1.7 (SO 4 ) 3 During high-rate charge and discharge of the positive electrode material, the crystal structure stability of the material is poor, the sodium ion deintercalation is hindered, and the electrochemical activity is lost rapidly.

[0078] Comparative Example 3 (1) Same as step (1) in Example 1; (2) The precursor solution obtained in step (1) is spray dried at 220°C and a creep speed of 35 rpm, and the precursor powder is divided into two portions, which are loaded into corundum magnetic boats in batches and placed in a tubular furnace. A high-purity argon atmosphere is first introduced for 2 hours, and the tubular furnace is evacuated. Then, the temperature is raised from room temperature to 250°C and 450°C at a rate of 2°C / min in a high-purity argon atmosphere, and then the temperature is kept at this temperature for 12 hours for heat treatment. The mixture is cooled to room temperature along with the furnace to obtain carbon nanotube-coated sodium ferrous phosphate sulfate positive electrode materials.

[0079] like Fig.19 As shown in the figure, the crystal structure of the carbon nanotube-coated sodium ferrous phosphate sulfate positive electrode material obtained in Comparative Example 3 of the present invention at different heat treatment temperatures is inconsistent with that in Example 1 of the present invention, and the peak shape is almost incompatible; this indicates that when the heat treatment temperature is 250°C, the crystal forming thermodynamics has not been reached and the target crystal is not formed; and when the heat treatment temperature is 450°C, SO 4 2- Decomposition occurs, and the carbon nanotube-coated Na 2.9 Fe 1.7 (SO 4 ) 2.7 (PO 4 ) 0.3 Positive electrode material.

Claims

1. A carbon-coated sodium ferrous phosphate sulfate positive electrode material, characterized in that: The carbon-coated sodium ferrous phosphate sulfate positive electrode material is a square flaky particle and irregular agglomerates formed by a conductive carbon material coating sodium ferrous phosphate sulfate; the molecular formula of the sodium ferrous phosphate sulfate is Na (6-2x+y) Fe x (SO4) (3-y) (PO4) y , where 0<x<3, 0<y≤0.

5.

2. The carbon-coated sodium ferrous phosphate sulfate positive electrode material according to claim 1, characterized in that: In the carbon-coated sodium ferrous phosphate sulfate positive electrode material, the mass fraction of the conductive carbon material is 1.0-5.0%; the conductive carbon material includes one or more of conductive carbon black, carbon fiber, graphene, reduced graphene oxide, fullerene or carbon nanotubes; the average particle size of the square flake particles is 1-5 μm, and the average thickness is 10-50 nm.

3. A method for preparing the carbon-coated sodium ferrous phosphate sulfate positive electrode material as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) dissolving a sodium source, a ferrous source and a sulfuric acid source in water, adjusting the pH value to acidic, and then sequentially adding a phosphoric acid source and a conductive carbon material slurry, stirring and mixing, to obtain a precursor solution; (2) After drying the precursor solution obtained in step (1), the obtained precursor powder is heat-treated under a protective atmosphere and cooled to room temperature in a furnace to obtain a carbon-coated sodium ferrous phosphate sulfate positive electrode material.

4. The method for preparing the carbon-coated sodium ferrous phosphate sulfate positive electrode material according to claim 3, characterized in that: In step (1), the molar volume ratios of the sodium ions, ferrous ions, sulfate ions, phosphate ions and water are 0.1-3.0 mol / L, 0.1-2.0 mol / L, 0.2-5.0 mol / L, and 0.1-0.5 mol / L, respectively; the mass fraction of the conductive carbon material slurry is 1-5%; the amount of the conductive carbon material slurry is such that the conductive carbon material accounts for 1-5% of the theoretical mass of the final product of the carbon-coated sodium ferrous phosphate sulfate positive electrode material; the pH value is adjusted to 3-4; an acidic medium or alkaline medium solution with a mass fraction of 5-20% is added dropwise to adjust the pH value; the acidic medium solution includes one or more of dilute sulfuric acid, ascorbic acid solution or citric acid solution; The alkaline medium solution includes one or more of sodium hydroxide solution, sodium carbonate solution or ammonia solution; the stirring and mixing temperature is 20-50° C., the stirring speed is 300-600 r / min, and the time is 5-60 min.

5. The method for preparing the carbon-coated sodium ferrous phosphate sulfate positive electrode material according to claim 3 or 4, characterized in that: In step (1), the sodium source includes one or more of sodium sulfate, sodium carbonate, sodium hydroxide, sodium nitrate or sodium phosphate, and their hydrates; the ferrous source includes ferrous sulfate and its hydrates; the sulfuric acid source includes one or more of sodium sulfate, ferrous sulfate, and their hydrates or sulfuric acid; the phosphate source includes one or more of diammonium phosphate, diammonium hydrogen phosphate, sodium phosphate, and their hydrates or phosphoric acid; the conductive carbon material includes one or more of conductive carbon black, carbon fiber, graphene, reduced graphene oxide, fullerene or carbon nanotubes.

6. The method for preparing the carbon-coated sodium ferrous phosphate sulfate positive electrode material according to any one of claims 3 to 5, characterized in that: In step (2), the drying is spray drying or freeze drying; the spray drying temperature is 150 to 240° C., and the peristaltic speed is 20 to 65 rpm.

7. The method for preparing the carbon-coated sodium ferrous phosphate sulfate positive electrode material according to any one of claims 3 to 6, characterized in that: In step (2), the protective atmosphere includes one or more of nitrogen, argon or helium; before the heat treatment, the protective atmosphere is introduced for 0.5 to 3.0 hours and the heat treatment device is evacuated; the heat treatment is carried out at a rate of 1 to 10°C / min, from room temperature to 350 to 400°C, and then kept warm for 6 to 24 hours.

8. An application of the carbon-coated sodium ferrous phosphate sulfate positive electrode material as claimed in claim 1 or 2, characterized in that: The positive electrode sheet made of the carbon-coated sodium ferrous phosphate sulfate positive electrode material according to claim 1 or 2 is used to assemble button-type, cylindrical, square or soft-pack sodium ion batteries.

Citation Information

Patent Citations

  • Lithium battery positive electrode material doped with rare-earth element and preparation method of lithium battery positive electrode material

    CN108550832A

  • Sulfate sodium ion battery positive electrode material with high air stability and preparation method thereof

    CN117594767A

  • Polyanionic positive electrode material, preparation method thereof and sodium ion battery

    CN117747815A

  • Sodium ferrous sulfate / sodium ferric phosphate composite positive electrode material for sodium ion battery and preparation method of sodium ferrous sulfate / sodium ferric phosphate composite positive electrode material

    CN118825266A

  • Positive electrode material for sodium-ion battery, and preparation method therefor and application thereof

    WO2023071396A1

Cited By

  • Sodium ferric sulfate composite sodium ion positive electrode material, preparation method thereof and battery

    CN120878796A

  • Lithium precipitation mother liquor recovery method, composite sodium ferrous sulfate material, positive pole piece and secondary battery

    CN121020660A

  • Lithium precipitation mother liquor recovery method, composite ferrous sulfate sodium material, positive electrode sheet, and secondary battery

    CN121020660B

  • Modified sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN121449109A

  • Preparation method of sodium ion battery positive electrode material, positive electrode material, sodium ion battery and electric equipment

    CN121735228A